Influence of silica architecture on the catalytic activity of immobilized glucose oxidase. Issue 1 (11th September 2018) - Begum, Gousia; Oschatz, Cathleen; Oschatz, Martin; Kaskel, Stefan; Brunner, Eike; Kröger, Nils
Abstract : Immobilizing enzymes on solid support materials is of great interest for many applications as it improves enzyme lifetime and enables its recycling. Synthetic mesoporous silica materials are widely used as supports for enzyme immobilization due to their high enzyme-loading capacity and their excellent mass transport properties through interconnected channels of mesopores. Much less is known about the enzyme support properties of naturally occurring mesoporous silica materials. These are readily available through the growth of diatoms, which biosynthesize hierarchically porous silica microshells with pore diameters ranging from 10 to 1000 nm. Here the authors investigated the performance as enzyme support materials of biosilica from three diatom species in comparison to synthetic silica materials. Using glucose oxidase (GOx) as a model enzyme, the authors determined the enzyme-loading capacities and the specific catalytic activities of the GOx-bearing (bio)silicas both under suspension conditions and in a flow-through setting. Remarkably, the specific activity of GOx was strongly dependent on the type of diatom biosilica material and in the best case was as high as on synthetic mesoporous silica. Porosity analysis of the materials points to an important role of large mesopores (diameters >20 nm) for supporting a high specific activity of (bio)silica-immobilized GOx.